Changes in Central Corneal Thickness, Corrected Intraocular Pressure, and Iridocorneal Angle in Unilateral Acute Anterior Uveitis - Pandey, Sumit; Kharel Sitaula, Ranju; Joshi, Sagun Narayan (Nepalese Journal of Ophthalmology, 2023)
Introduction: The release of inflammatory mediators in the anterior chamber can lead to the structural alteration of the corneal and uveal tissue.Objectives: To compare the changes in Central Corneal Thickness (CCT), corrected Intraocular Pressure (cIOP) and Iridocorneal Angle (ICA) in unilateral acute anterior uveitis (AAU) before and after treatment.Materials and methods: The study was a hospital based comparative study conducted between July 2018 to June 2019. Newly diagnosed, untreated unilateral Acute Anterior Uveitis (AAU) adult cases above 16 years were included in the study. Ethical clearance was obtained from the Institutional Review Committee of Institute of Medicine. Eighty-two unilateral AAU cases (Total 164 eyes including 82 unaffected were analyzed) underwent Goldmann applanation tonometry (GAT) and corneal topography at presentation and three weeks after treatment. The cIOP was calculated by the Ehlers formula.Results: The mean CCT of affected eyes was greater (563.84±51.49μm) compared to unaffected eyes (535.99±31.48μm) before treatment (p=0.001) and was reduced (533.2±25.71μm) after treatment (p=0.01). There was no significant difference in IOP, cIOP, and ICA between the affected eyes (14.45±6.89mmHg, 13.14±7.14mmHg and 48.78±7.94°) and the unaffected eyes (14.02±2.36mmHg, 14.4±3.09mmHg, and 49.80°±8.21°) before treatment. There was no difference in IOP (14.04±2.76mmHg) and ICA (49.21°±6.72°) after treatment, however, there was a significant increase (p=0.01) in the cIOP (14.95±2.93mmHg).Conclusion: In the study, CCT of affected eyes was greater compared to unaffected eyes and reduced after treatment. There was no difference in cIOP and ICA in case eyes compared to control before treatment. However, cIOP increased after treatment.